HUMAN CAPITAL SEBAGAI BAGIAN DARI INTELLIGENT CAPITAL DALAM DAYA SAING PERUSAHAAN - Ivan, M.P. Brata; Nur Wening (Pusat Riset dan Inovasi Nasional, 2023)
Human Capital as a part of Intelligent Capital in Company Competitiveness. Every single company’s final goal is to make a profit business. Company market competitiveness is a manifestation of its both performance and quality. The competition demands a well – arranged company resources and capitals include its Intelligent Capital which contain Human Capital. A good Intelligent Capitaled Company indicates by its competent Human Capital, to make sure the company are qualified and well performed enough to be a strong competitor in the market.